2010
DOI: 10.1038/gt.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Studies on protective effects of human paraoxonases 1 and 3 on atherosclerosis in apolipoprotein E knockout mice

Abstract: Paraoxonase (PON) possesses antiatherogenic potentials, but the distinct functions of PON members in alleviating atherosclerosis are not yet clear. This study aimed to evaluate the protective effects of hPON1 and hPON3 against atherosclerosis, and thereby exploring their synergistic mechanism in atherosclerosis development. We generated the recombinant adenovirus AdPON1 and AdPON3, which were capable of expressing hPON1 and hPON3. After AdPON1 and AdPON3 were injected intravenously into 5-week-old apolipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
(43 reference statements)
0
32
0
Order By: Relevance
“…On the other hand, the overexpression of human PON3 in mouse models of atherosclerosis results in no HDL-associated PON3 in mouse circulation, but human PON3 was expressed in several mouse tissues [17,22]. Expression of PON3 significantly reduced atherosclerosis; however, all the effects appeared to be Reasons for these differences are unclear; however, differences in gene expression between monocytes isolated from blood and those infiltrating the aortic wall cannot be ruled out.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…On the other hand, the overexpression of human PON3 in mouse models of atherosclerosis results in no HDL-associated PON3 in mouse circulation, but human PON3 was expressed in several mouse tissues [17,22]. Expression of PON3 significantly reduced atherosclerosis; however, all the effects appeared to be Reasons for these differences are unclear; however, differences in gene expression between monocytes isolated from blood and those infiltrating the aortic wall cannot be ruled out.…”
Section: Discussionmentioning
confidence: 68%
“…However, a recent study in apo-E-deficient mice showed that the injection of human recombinant PON3 decreased plaque size without changes in lipid peroxidation levels [22].…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus based overexpression of human PON1 in apolipoprotein E knock-out mice is associated with reduced TNF␣ levels (43). Serum PON1 activity is correlated to serum TNF␣ levels in atheromatous patients with RA (44) and TNF␣ antagonist therapy leads to enhanced PON1 levels, heightened antioxidant capacity of HDL and a reduced inflammatory status (11).…”
Section: Discussionmentioning
confidence: 99%
“…PON1 and PON3 differ in their expression profile, protein localization, and enzymatic activity, but are considered to have similar effects on the hydrolysis of oxidized lipids and promotion of macrophage cholesterol efflux in experimental models 70 . Although low levels of PON1 activity were associated with a modest inverse risk of CHD in a population-based study, this relationship was abolished after adjustment for HDL-C and apoA-I, suggesting that low PON1 activity is not a causal factor in atherogenesis 71 .…”
Section: Hdl Functionality and Atherosclerosismentioning
confidence: 99%